The Perception of Quality Nursing Work Environment among Hospital Nurses - Aric Vranada; Chiou-Fen Lin; Chia-Jung Hsieh; Tsae-Jyy Wang (Alta Dharma Publisher, 2021)
Background: Nurses, the more significant health care provider, need an excellent work environment that adequately expresses their skills and knowledge on providing optimum care quality outcomes to the patients. Objective: This study aimed to determine the current state of the nurses’ perceived work environment quality and examine differences in perceived work environment quality among nurses with different characteristics. Method: A descriptive cross-sectional correlation design and a probability sampling method recruit 334 hospital nurses. The self-report questionnaire scale of the Quality Nursing Work Environment (QNWE) was used to collect data. Descriptive statistics, variant analysis (ANOVA), independent-sample t-test, and Pearson correlation were utilized to analyze comprehensive data. Result: The participants reported a perceived moderate level of quality of the work environment. The perceived QNWE levels were found to differ across participants' ages statistically (p<0.05), work experience (p<0.01), and department (p<0.05). Most participants rated their working environment as high quality on the domain